New Shocks, Exchange Rates and Equity Prices - Cova, Pietro (IMF Working Papers; Working Paper ;, 2008)
We study exchange rate and equity price dynamics, in general equilibrium, in the presence of news shocks about future productivity and monetary policy. We identify a condition under which these asset prices become more volatile without affecting the volatility of the underlying processes-a positive correlation between news and current shocks. This condition also explains why persistent underlying processes generate volatile asset prices. In addition, we show that the correlation between exchange rate and equity returns depends critically on the currency denomination of the equity return and the monetary policy reaction to productivity shocks. The model we set up does well at matching second moments of exchange rate and equity returns for major floating currencies.